Proposed Marketing Strategy to Increase Willingness to Use Livin’ Sukha for Shopping at Alfamart - Nensy Praninta Simanjuntak; Atik Aprianingsih (Jurnal Riset Ekonomi dan Akuntansi, 2026)
The growth of digital banking services has inspired banks in Indonesia to provide a package of services not limited to financial transaction purposes but also lifestyle commerce and shopping. Yet, it is observed that the use of the Livin’ Sukha service in the Livin’ by Mandiri app is quite low compared to other digital banking services. Therefore, this study will examine the effect of perceived benefits, perceived risk, and perceived trust on customers' willingness to use Livin’ Sukha services for shopping activities at Alfamart. For this purpose, a quantitative research design was applied by utilizing a survey research methodology with a sample of 200 users of Livin’ by Mandiri, selected using purposive sampling technique. The data were gathered by distributing online surveys and analyzed using Structural Equation Modeling based on Partial Least Square. It was discovered that there is a positive relationship between perceived benefits and perceived trust and perceived benefits and willingness to use; meanwhile, perceived risk showed negative relationships with perceived trust and willingness to use. Furthermore, perceived trust has positive relationships with customers' willingness to use Livin’ Sukha services. Besides, it has been revealed that household shopping activities have good potential to increase customers' engagement and transactions